STRATEGI VISUAL IKLAN TELEVISI KUKU BIMA ENERGI PRODUKSI PT. SIDO MUNCUL SEMARANG - Annas Marzuki Sulaiman; I Nyoman Murtana (Gelar : Jurnal Seni Budaya, 2015)
Kuku Bima Energi is a brand of an energy drink produced by P.T. Sido Muncul, Semarang. Sido Muncullaunches an advertisement of version Mari Berwisata di Negeri Sendiri (Let’s go touring in our own country).The research is purposed to describe: 1). background of PT. Sido Muncul represents television advertisementKuku Bima Energy version Mari Berwisata di Negeri Sendiri; 2). Visual strategy of television advertisementKuku Bima Energy version Mari Berwisata di Negeri Sendiri; and 3). Visual form of television advertisementKuku Bima Energy version Mari Berwisata di Negeri Sendiri. The research uses qualitative method and casestudy approach. The research process is arranged based on the data gaining and correlation in order toaccumulate information related to visual strategy and advertisement structure. The analysis used is aestheticsMonroe Beardsley. The result of research shows that Kuku Bima Energi in its imaging has been succeed inusing the nationalism issues to bind consumers by raising up the cultural and tourism values through televisionadvertisement. It makes the nationalist image and love to local culture attached to Kuku Bima Energi and hasbound consumers emotionally.Keywords: Kuku Bima Energy, Brand, imaging, visual strategy, aesthetics